Enhanced fully-sulfonated polyimide proton exchange membrane and preparation method thereof

By forming a polyimide layer in the ePTFE layer and using tannin treatment, combined with scraper coating technology, the mechanical strength and chemical stability of the proton exchange membrane are improved, and the problem of contradiction in the performance of the proton exchange membrane in the prior art is solved. , achieving efficient proton conduction and stable fuel cell performance.

CN119153741APending Publication Date: 2024-12-17SUSHUI NEW MATERIAL (SHANGHAI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411288618.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

There is a performance contradiction between the existing proton exchange membranes in improving proton conduction capability and mechanical stability, resulting in limited energy efficiency and life of fuel cells and high cost.

Method used

Using an enhanced fully sulfonated polyimide proton exchange membrane, a polyimide layer is formed in the ePTFE layer and the ePTFE layer is treated with tannic acid and tetraethylene pentamine to form a hydrophilic proton exchange membrane reinforcement layer. , combined with scraper coating technology to control the thickness and structure of the composite film, improve the mechanical strength and chemical stability of the film.

Benefits of technology

It realizes improving proton conduction performance and mechanical stability in fuel cells, reducing the cost and manufacturing cost of fuel cells, extending the service life of fuel cells, and suitable for direct methanol fuel cells and other types of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153741A_ABST
    Figure CN119153741A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of proton exchange membranes, and particularly relates to an enhanced fully-sulfonated polyimide proton exchange membrane and a preparation method thereof, the enhanced fully-sulfonated polyimide proton exchange membrane comprises an ePTFE layer and a polyimide layer; the number of the polyimide layers is two, the two polyimide layers are formed on the two sides of the ePTFE layer respectively, and pores of the ePTFE layer are filled with the polyimide layers. The preparation method of the enhanced fully-sulfonated polyimide proton exchange membrane comprises the following specific steps: S1, pre-treating ePTFE; s2, fully sulfonated polyimide is prepared; and S3, preparing the composite membrane. The mechanical strength and the chemical stability of the membrane are improved, and meanwhile, the excellent proton conduction performance is ensured. The development of the technology has important practical significance and application prospect for improving the energy efficiency and the service life of the fuel cell and reducing the manufacturing cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of proton exchange membranes, in particular to an enhanced fully sulfonated polyimide proton exchange membrane and a preparation method thereof. Background Art

[0002] Proton exchange membrane (PEM) is a core component in fuel cell systems. Its main function is to effectively transfer protons while blocking the permeation of anode fuel. The most widely used proton exchange membranes on the market are the Nafion series. The main chain of this membrane is composed of a perfluorocarbon chain, and the side chain is connected to a sulfonic acid group. Nafion membrane is widely used due to its excellent chemical stability and excellent mechanical properties, but its high cost, large fuel permeability and strict requirements on operating environment temperature and humidity limit its feasibility in a wider range of applications.

[0003] In recent years, sulfonated polyimide (SPI) has become a research hotspot due to its low cost, excellent mechanical properties and thermal stability, and flexible molecular design. SPI is synthesized by the polymerization reaction of dianhydride and diamine monomers, and its hydrophilicity and proton conductivity are enhanced by introducing sulfonic acid groups. According to the Grotthuss mechanism and transport mechanism, proton exchange membranes are more effective in transferring protons in a hydrated environment. Low hydration increases the activation energy of proton transfer, thereby reducing the transfer efficiency. As the content of sulfonic acid groups increases, although the proton conductivity can be improved, it also causes the membrane to absorb water and swell, which not only reduces the mechanical stability of the membrane, but also shortens its service life. This performance contradiction is the main challenge facing the current technology.

[0004] To solve this problem, a common method is to compound expanded polytetrafluoroethylene (ePTFE) as a reinforcing material into the proton exchange membrane, using its excellent mechanical properties to improve the overall stability and anti-swelling ability of the membrane. However, ePTFE itself is not conductive and easily phase separates from conductive polymers, which to a certain extent limits its role in improving the performance of proton exchange membranes. Therefore, the development of a new proton exchange membrane that has both high proton conductivity and significantly improved membrane mechanical stability is a key issue that needs to be urgently addressed in the current development of proton exchange membrane technology. Summary of the invention

[0005] The object of the present invention is to provide an enhanced fully sulfonated polyimide proton exchange membrane and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: an enhanced fully sulfonated polyimide proton exchange membrane, comprising:

[0007] ePTFE layer, polyimide layer;

[0008] The polyimide layer is provided with two layers, the two polyimide layers are respectively formed on both sides of the ePTFE layer, and the polyimide layers are filled into the pores of the ePTFE layer;

[0009] The ePTFE layer is treated with tannic acid and tetraethylenepentamine, and the ePTFE layer treated with tannic acid constitutes a hydrophilic proton exchange membrane reinforcement layer.

[0010] Preferably, the ePTFE layer has a thickness of 6-8 microns, a pore size of 0.1-0.45 microns, a porosity of 80-90%, and the polyimide layer has a thickness of 8-10 microns.

[0011] Preferably, the ePTFE layer is directly immersed in the polyimide solution, taken out after being fully immersed, and a polyimide layer is formed on both sides of the ePTFE layer. The ePTFE layer and the polyimide layer are coated with a scraper to control the thickness of the composite film formed by the ePTFE layer and the polyimide layer to be 14-20 microns.

[0012] A method for preparing the enhanced fully sulfonated polyimide proton exchange membrane, the specific steps of the method for preparing the enhanced fully sulfonated polyimide proton exchange membrane are as follows:

[0013] S1: ePTFE pretreatment: The ePTFE membrane is clamped and fixed with a polytetrafluoroethylene frame and immersed in Tris-HCl buffer. 1000-2000 mg of tannic acid is added to the Tris-HCl buffer to fully dissolve the tannic acid. After dissolution, tetraethylenepentamine is added. After the ePTFE membrane is immersed in the tannic acid solution for a predetermined time, the residual tannic acid on the surface of the ePTFE layer is washed away with deionized water. The cleaned ePTFE membrane is dried for later use.

[0014] S2: Preparation of fully sulfonated polyimide: 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4'-di(4-aminophenoxy)biphenyl-3,3-disulfonic acid were placed in an oven at 130°C and dried for 6 hours to fully remove the water molecules in the monomers. A 100ml three-necked bottle was taken and fully dried under nitrogen to remove the water vapor in the bottle. For linear polymers, 1mmol of BAPBDS and 1-2ml of triethylamine were added to 5-10ml of m-cresol, and stirred at room temperature under nitrogen protection until completely dissolved. 1.75-2g of benzoic acid and 1mmol of NTDA anhydride monomer were added, and the reaction was carried out at 80°C for 6 hours, and the temperature was raised to 150°C for 24 hours. Benzoic acid, triethylamine and m-cresol were removed with 80ml of acetone under magnetic stirring, and the dark brown filter cake was collected and vacuum dried at 130°C for 4 hours.

[0015] S3: Preparation of composite membrane: The NTDA-BAPBDS synthesized in step S2 is dissolved in a solvent to prepare a solution with a mass concentration of 10%. The polytetrafluoroethylene porous membrane with surface hydrophilic treatment is immersed in the prepared NTDA-BAPBDS solution for 12 hours, then slowly pulled out, placed on a glass plate and flattened with a wire rod to remove bubbles and ensure that the surface is covered with a layer of SPI solution. The membrane is fixed with clips on all sides and the prepared ePTFE-SPI composite membrane is placed in an oven at 80°C and dried for 24 hours.

[0016] Preferably, the modified ePTFE is fully immersed in the polyimide solution, the immersed ePTFE is taken out and flattened on a glass sheet, and a scraper is used to scrape to remove bubbles in the membrane. The thickness of the composite membrane is controlled between 14 and 20 microns by scraping with the scraper. The prepared composite membrane is placed in a vacuum oven to dry to completely evaporate the solvent and solidify the polyimide on the ePTFE; annealing is performed at high temperature to finally obtain a proton exchange membrane.

[0017] Preferably, in step S1, the pore size of the ePTFE membrane is one of 0.1 micron, 0.22 micron or 0.45 micron.

[0018] Preferably, in step S3, the solvent is one of dimethyl sulfoxide, m-cresol, N,N-dimethylformamide and N-dimethylacetamide.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] Enhanced proton exchange membranes are suitable for various fuel cell systems, especially in direct methanol fuel cells (DMFCs) and other types of fuel cells. Through special structural design and material selection, the mechanical strength and chemical stability of the membrane are improved, while ensuring excellent proton conductivity. The development of this technology has important practical significance and application prospects for improving the energy efficiency and life of fuel cells and reducing manufacturing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Cross-sectional view of enhanced fully sulfonated polyimide proton exchange membrane

[0022] Figure 2 It is a diagram of the synthesis process of NTDA-BAPBDS;

[0023] Figure 3 This is the surface image of the ePTFE membrane that has not been treated with tannic acid;

[0024] Figure 4 SEM images of ePTFE membranes with different pores;

[0025] Figure 5Conductivity graphs of the four composite films at different temperatures and relative humidity of 100% RH;

[0026] Figure 6 Tensile strength test diagram of four composite films. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0029] Embodiment 1:

[0030] See also Figure 1-6 , the present invention provides a technical solution: 1. An enhanced fully sulfonated polyimide proton exchange membrane, comprising: an ePTFE layer and a polyimide layer;

[0031] The polyimide layer is provided with two layers, and the two polyimide layers are respectively formed on both sides of the ePTFE layer, and the polyimide layer is filled into the pores of the ePTFE layer; the ePTFE layer is treated with tannic acid and tetraethylenepentamine, and the ePTFE layer treated with tannic acid constitutes a hydrophilic proton exchange membrane reinforcement layer. The thickness of the ePTFE layer is 6-8 microns, the pore size is 0.1-0.45 microns, the porosity is 80-90%, and the thickness of the polyimide layer is 8-10 microns. The ePTFE layer is directly immersed in the polyimide solution, and is taken out after being fully immersed. Polyimide layers are formed on both sides of the ePTFE layer, and a scraper is used for scraping to control the thickness of the composite membrane formed by the ePTFE layer and the polyimide layer to be 14-20 microns.

[0032] A method for preparing an enhanced fully sulfonated polyimide proton exchange membrane, the specific steps of the method for preparing the enhanced fully sulfonated polyimide proton exchange membrane are as follows:

[0033] S1: ePTFE pretreatment: The ePTFE membrane is clamped and fixed with a polytetrafluoroethylene frame and immersed in Tris-HCl buffer. 1000-2000 mg of tannic acid is added to the Tris-HCl buffer to fully dissolve the tannic acid. After dissolution, tetraethylenepentamine is added. After the ePTFE membrane is immersed in the tannic acid solution for a predetermined time, the residual tannic acid on the surface of the ePTFE layer is washed away with deionized water. The cleaned ePTFE membrane is dried for use. The pore size of the ePTFE membrane is one of 0.1 micron, 0.22 micron or 0.45 micron.

[0034] S2: Preparation of fully sulfonated polyimide: 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4'-di(4-aminophenoxy)biphenyl-3,3-disulfonic acid were placed in an oven at 130°C and dried for 6 hours to fully remove the water molecules in the monomers. A 100ml three-necked bottle was taken and fully dried under nitrogen to remove the water vapor in the bottle. For linear polymers, 1mmol of BAPBDS and 1-2ml of triethylamine were added to 5-10ml of m-cresol, and stirred at room temperature under nitrogen protection until completely dissolved. 1.75-2g of benzoic acid and 1mmol of NTDA anhydride monomer were added, and the reaction was carried out at 80°C for 6 hours, and the temperature was raised to 150°C for 24 hours. Benzoic acid, triethylamine and m-cresol were removed with 80ml of acetone under magnetic stirring, and the dark brown filter cake was collected and vacuum dried at 130°C for 4 hours.

[0035] S3: Preparation of composite membrane: The NTDA-BAPBDS synthesized in step S2 is dissolved in a solvent (the solvent is one of dimethyl sulfoxide, m-cresol, N,N-dimethylformamide, and N-dimethylacetamide) to prepare a solution with a mass concentration of 10%. The polytetrafluoroethylene porous membrane with surface hydrophilic treatment is immersed in the prepared NTDA-BAPBDS solution for 12 hours, then slowly pulled out, placed on a glass plate and flattened with a wire rod to remove bubbles and ensure that the surface is covered with a layer of SPI solution. The membrane is fixed with clips on all sides, and the prepared ePTFE-SPI composite membrane is placed in an oven at 80°C and dried for 24 hours.

[0036] The modified ePTFE is fully immersed in the polyimide solution, the immersed ePTFE is taken out and flattened on a glass sheet, and a scraper is used to scrape it to remove bubbles in the membrane. The thickness of the composite membrane is controlled between 14 and 20 microns by scraping with the scraper. The prepared composite membrane is placed in a vacuum oven to dry, so that the solvent can be completely evaporated and the polyimide is solidified on the ePTFE; it is annealed at high temperature to finally obtain a proton exchange membrane.

[0037] Example 1

[0038] This embodiment relates to a tannic acid-modified enhanced proton exchange membrane and a preparation method thereof, which is coated by a doctor blade and comprises the following steps:

[0039] The polymer was dissolved in m-cresol to prepare an SPI solution (10 wt % fully sulfonated polyimide resin solution) and mixed. The mixture was stirred mechanically by a magnetic device with a rotation speed set to 500 rpm for 3 hours and ultrasonically stirred for 15 minutes to completely dissolve the fully sulfonated polyimide polymer.

[0040] The ePTFE was fixed by a polytetrafluoroethylene frame and immersed in Tris-Hcl buffer. 1000-2000 mg of tannic acid (TA) was added to the buffer to fully dissolve it. After dissolution, tetraethylenepentamine (TEPA) was added. After soaking in the tannic acid solution for a predetermined time, the residual tannic acid was washed away with deionized water, and the modified ePTFE membrane was dried for later use.

[0041] The ePTFE membrane with a pore size of 0.1 micron and a porosity of 80% was treated with tannic acid and directly immersed in the polyimide solution for 12 hours. After being fully immersed, it was taken out and scraped with a scraper to control the thickness of the composite membrane to be 14-20 microns. During the scraping process, bubbles in the membrane were removed and the membrane surface was kept flat.

[0042] The membrane was clamped on the substrate with a metal frame to fix it. The coated membrane was then placed in an oven for heat treatment. The heat treatment conditions were: first step, 80°C, time 12h; second step, 150°C, time 6h. Finally, an enhanced fully sulfonated polyimide proton exchange membrane with an ePTFE pore size of 0.1 micron was obtained.

[0043] Example 2

[0044] This embodiment relates to a tannic acid-modified enhanced proton exchange membrane and a preparation method thereof, which is coated by a doctor blade and comprises the following steps:

[0045] The polymer was dissolved in m-cresol to prepare an SPI solution (10 wt % fully sulfonated polyimide resin solution) and mixed. The mixture was stirred mechanically by a magnetic device with a rotation speed set to 500 rpm for 3 hours and ultrasonically stirred for 15 minutes to completely dissolve the fully sulfonated polyimide polymer.

[0046] The ePTFE was fixed by a polytetrafluoroethylene frame and immersed in Tris-Hcl buffer. 1000-2000 mg of tannic acid (TA) was added to the buffer to fully dissolve it. After dissolution, tetraethylenepentamine (TEPA) was added. After soaking in the tannic acid solution for a predetermined time, the residual tannic acid was washed away with deionized water, and the modified ePTFE membrane was dried for later use.

[0047] The ePTFE layer with a thickness of 0.22 microns and a porosity of 90% is directly immersed in the polyimide solution for 12 hours, taken out after being fully immersed, and scraped with a scraper to control the thickness of the composite film to be 14-20 microns. During the scraping process, bubbles in the film are removed and the surface of the film is kept flat.

[0048] The membrane was clamped on the substrate with a metal frame to fix it. The coated membrane was then placed in an oven for heat treatment. The heat treatment conditions were: first step, 80°C, time 12h; second step, 150°C, time 6h. Finally, an enhanced fully sulfonated polyimide proton exchange membrane with an ePTFE pore size of 0.22 microns was obtained.

[0049] Example 3

[0050] This embodiment relates to a tannic acid-modified enhanced proton exchange membrane and a preparation method thereof, which is coated by a doctor blade and comprises the following steps:

[0051] The polymer was dissolved in m-cresol to prepare an SPI solution (10 wt % fully sulfonated polyimide resin solution) and mixed. The mixture was stirred mechanically by a magnetic device with a rotation speed set to 500 rpm for 3 hours and ultrasonically stirred for 15 minutes to completely dissolve the fully sulfonated polyimide polymer.

[0052] The ePTFE was fixed by a polytetrafluoroethylene frame and immersed in Tris-Hcl buffer. 1000-2000 mg of tannic acid (TA) was added to the buffer to fully dissolve it. After dissolution, tetraethylenepentamine (TEPA) was added. After soaking in the tannic acid solution for a predetermined time, the residual tannic acid was washed away with deionized water, and the modified ePTFE membrane was dried for later use.

[0053] The 0.45 micron, 90% porosity ePTFE layer treated with tannic acid was directly immersed in the polyimide solution for 12 hours, taken out after full immersion, and scraped with a scraper to control the thickness of the composite film to be 14-20 microns. During the scraping process, remove the bubbles in the film and keep the surface of the film flat.

[0054] The membrane was clamped on the substrate with a metal frame to fix it. The coated membrane was then placed in an oven for heat treatment. The heat treatment conditions were: first step, 80°C, time 12h; second step, 150°C, time 6h. Finally, an enhanced fully sulfonated polyimide proton exchange membrane with an ePTFE pore size of 0.45 microns was obtained.

[0055] Comparative Example 1

[0056] In this comparative example, the fully sulfonated polyimide proton exchange membrane and the preparation method thereof are coated by a doctor blade and include the following steps:

[0057] The polymer was dissolved in m-cresol to prepare an SPI solution (10 wt % fully sulfonated polyimide resin solution) and mixed. The mixture was stirred mechanically by a magnetic device with a rotation speed set to 500 rpm for 3 hours and ultrasonically stirred for 15 minutes to completely dissolve the fully sulfonated polyimide polymer.

[0058] The prepared resin solution is evenly coated on the glass substrate, and a scraper is used for scraping to control the thickness of the composite film to be 14-20 microns. During the scraping process, bubbles in the film are removed and the film surface is kept flat.

[0059] The coated membrane was then placed in an oven for heat treatment, and the heat treatment conditions were: first step, 80° C., time 12 h; second step, 150° C., time 6 h. Finally, a fully sulfonated polyimide proton exchange membrane was obtained.

[0060] Comparative Example 2

[0061] In this comparative example, the enhanced proton exchange membrane not modified with tannic acid and the preparation method thereof are coated with a doctor blade, comprising the following steps:

[0062] The polymer was dissolved in m-cresol to prepare an SPI solution (10 wt % fully sulfonated polyimide resin solution) and mixed. The mixture was stirred mechanically by a magnetic device with a rotation speed set to 500 rpm for 3 hours and ultrasonically stirred for 15 minutes to completely dissolve the fully sulfonated polyimide polymer.

[0063] The 0.22 micron ePTFE layer with a porosity of 90% is directly immersed in the polyimide solution for 12 hours, taken out after being fully immersed, and scraped with a scraper to control the thickness of the composite film to be 14-20 microns. During the scraping process, bubbles in the film are removed and the surface of the film is kept flat.

[0064] The membrane was clamped on the substrate with a metal frame to fix it. The coated membrane was then placed in an oven for heat treatment. The heat treatment conditions were: first step, 80°C, time 12h; second step, 150°C, time 6h. Finally, an enhanced fully sulfonated polyimide proton exchange membrane with an ePTFE pore size of 0.22 microns was obtained.

[0065] Performance Tests of Examples and Comparative Examples

[0066] The tensile tester (CMT4204, Meters Industrial Systems (China) Co., Ltd., USA) was selected to test the tensile force of the proton exchange membrane using the standard number: GB / T 20042.3-2022 Proton Exchange Membrane Test Method. The test sample size was 50mm×20mm, and the test rate was 50mm min-1. The activation area of ​​the assembled single cell was 6.25cm2, the fuel cell temperature was 80℃, the back pressure was 0.1MPa, and the fuel gas was methanol and oxygen. The performance of the fuel cell at 100% RH was tested. In order to evaluate the conductivity of the enhanced membrane, the proton conductivity test was carried out, and the effects of ePTFE membranes with different pore sizes on the conductivity were compared. The methanol permeability test was used to explore whether tannic acid modification can improve the prevention of methanol penetration.

[0067] Figure 1 A cross-sectional view of a reinforced fully sulfonated polyimide proton exchange membrane is shown, in which the polyimide runs through the ePTFE and wraps the ePTFE reinforcement layer in the middle.

[0068] Figure 2 This is the synthesis process of NTDA-BAPBDS.

[0069] Figure 3 (a) is the surface of the ePTFE membrane that has not been treated with tannic acid. (b) is the surface of the ePTFE membrane that has been treated with tannic acid, with a light yellow solid attached to the membrane surface. (b) is the SEM image of the ePTFE membrane that has not been treated with tannic acid, and the contact angle is measured to be 132°. (e) is the SEM image of the ePTFE membrane that has been treated with tannic acid, and the contact angle is measured to be 90°. The hydrophilicity is improved. The catechol in the tannic acid and the amine group in the tetraethylenepentamine can undergo a Michael addition reaction to form a CN bond, which is then polymerized on the surface of the ePTFE fiber, leaving tannic acid hydroxyl sites on the surface of the ePTFE after immersion. Through SEM observation, it was found that the diameter of the ePTFE changed from 200 nanometers to 280 nanometers. (c) is a cross-sectional view of the membrane after the ePTFE membrane treated with tannic acid is composited with polyimide. The polymer fully wraps the ePTFE. On the one hand, the treatment of tannic acid enhances the hydrophilicity of ePTFE, allowing the polyimide solution to fully infiltrate its voids. On the other hand, the tea phenol structure in tannic acid easily loses a hydrogen ion to show electronegativity, and can form hydrogen bonds with the oxygen of the sulfonic acid group and the oxygen of the diamine main chain in BAPBDS. These two forces synergistically alleviate the shuttle effect and inhibit the migration of sulfonated polyimide. (f) is a plan view of the membrane after the ePTFE membrane treated with tannic acid and the composite of polyimide. The surface is smooth and flat.

[0070] Figure 4The SEM images of ePTFE membranes with different pore sizes are shown in Figure 1. (a), (b), and (c) are the surfaces of the base membranes with pore sizes of 0.1, 0.22, and 0.45 microns, respectively; (d), (e), and (f) are the cross-sections of the base membranes with pore sizes of 0.1, 0.22, and 0.45 microns, respectively; and (g), (h), and (i) are schematic diagrams of the construction of proton transport channels in composite membranes with pore sizes of 0.1, 0.22, and 0.45 microns, respectively. Figure 4 The results in (a) show that the schematic diagram means that the conductivity of the reinforced composite membrane prepared by using small-pore ePTFE with a pore size of 0.1 μm is improved. The reason is that the hydrophilic sulfonic acid groups of polyimide will aggregate with each other to form large clusters when there is no constraint. However, the large clusters have poor connectivity due to the large radius, resulting in an "island effect", which is not conducive to the construction of a continuous proton transport channel. Therefore, the small pore size of ePTFE limits the disordered aggregation of the sulfonic acid groups of polyimide. This method controls the diameter of the proton transport channel formed by the sulfonic acid groups to better meet the demand for proton conduction.

[0071] Figure 5 The conductivity of the four composite membranes at different temperatures and relative humidity of 100% RH, the conductivity performance of Example 1 at the four temperatures is better than that of the other implementation groups and the control group. It can be seen that the small-pore ePTFE membrane plays a key role in forming an effective proton transport channel by limiting the disordered arrangement of sulfonic acid groups in polyimide, thereby improving the proton conductivity.

[0072] Figure 6 The tensile strength test of the four composite membranes showed that compared with the comparative example 1, the tensile strength of Examples 1, 2, and 3 was about twice that of the comparative example 1. This was because the ePTFE was compounded in the membrane, which significantly improved the tensile strength of the membrane.

[0073] Table 1 summarizes the enhanced membrane structures and main performance indicators prepared in the examples and comparative examples. It can be seen that when ePTFE is not used as a composite membrane in comparative example 1, the tensile strength is low, indicating that ePTFE enhances the tensile strength of the membrane. It is observed through comparative example 2 that when tannic acid is not used to treat the surface of ePTFE, its methanol permeability is about twice that of the ePTFE membrane treated with tannic acid under the same conditions, indicating that the enhanced proton exchange membrane treated with tannic acid reduces the methanol permeability. In addition, when ePTFE is not used to enhance the membrane in comparative example 1, the conductivity of the membrane is lower than that of the example, because the disordered arrangement of the sulfonic acid groups in the polyimide leads to fewer effective proton transmission channels.

[0074] In summary, the steps of the present invention are simple. Tannic acid is used to modify the ePTFE skeleton so that it is polymerized on the surface of ePTFE, and the phenolic hydroxyl groups on the tannic acid are used to describe the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essential content of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be arbitrarily combined with each other, and the pore size of the membrane includes but is not limited to the three pore sizes in the embodiments. The methods of changing the pore size to control the conductivity of the proton exchange membrane are all within the scope of protection of this patent.

[0075]

[0076]

[0077] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description. Therefore, it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention, and any figure marks in the claims should not be regarded as limiting the claims involved.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An enhanced fully sulfonated polyimide proton exchange membrane, characterized in that: include: ePTFE layer, polyimide layer; The polyimide layer is provided with two layers, the two polyimide layers are respectively formed on both sides of the ePTFE layer, and the polyimide layers are filled into the pores of the ePTFE layer; The ePTFE layer is treated with tannic acid and tetraethylenepentamine, and the ePTFE layer treated with tannic acid constitutes a hydrophilic proton exchange membrane reinforcement layer.

2. The proton exchange membrane reinforcement layer according to claim 1, characterized in that: The ePTFE layer has a thickness of 6-8 microns, a pore size of 0.1-0.45 microns, and a porosity of 80-90%. The polyimide layer has a thickness of 8-10 microns.

3. The proton exchange membrane reinforcement layer according to claim 1, characterized in that: The ePTFE layer is directly immersed in the polyimide solution, and taken out after being fully immersed. Polyimide layers are formed on both sides of the ePTFE layer, and a scraper is used for scraping to control the thickness of the composite film formed by the ePTFE layer and the polyimide layer to be 14-20 microns.

4. A method for preparing the enhanced fully sulfonated polyimide proton exchange membrane according to any one of claims 1 to 3, characterized in that: The specific steps of the preparation method of the enhanced fully sulfonated polyimide proton exchange membrane are as follows: S1: ePTFE pretreatment: The ePTFE membrane is clamped and fixed with a polytetrafluoroethylene frame and immersed in Tris-HCl buffer. 1000-2000 mg of tannic acid is added to the Tris-HCl buffer to fully dissolve the tannic acid. After dissolution, tetraethylenepentamine is added. After the ePTFE membrane is immersed in the tannic acid solution for a predetermined time, the residual tannic acid on the surface of the ePTFE layer is washed away with deionized water. The cleaned ePTFE membrane is dried for later use. S2: Preparation of fully sulfonated polyimide: 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4'-di(4-aminophenoxy)biphenyl-3,3-disulfonic acid were placed in an oven at 130°C and dried for 6 hours to fully remove the water molecules in the monomers. A 100ml three-necked bottle was taken and fully dried under nitrogen to remove the water vapor in the bottle. For linear polymers, 1mmol of BAPBDS and 1-2ml of triethylamine were added to 5-10ml of m-cresol, and stirred at room temperature under nitrogen protection until completely dissolved. 1.75-2g of benzoic acid and 1mmol of NTDA anhydride monomer were added, and the reaction was carried out at 80°C for 6 hours, and the temperature was raised to 150°C for 24 hours. Benzoic acid, triethylamine and m-cresol were removed with 80ml of acetone under magnetic stirring, and the dark brown filter cake was collected and vacuum dried at 130°C for 4 hours. S3: Preparation of composite membrane: The NTDA-BAPBDS synthesized in step S2 is dissolved in a solvent to prepare a solution with a mass concentration of 10%. The polytetrafluoroethylene porous membrane with surface hydrophilic treatment is immersed in the prepared NTDA-BAPBDS solution for 12 hours, then slowly pulled out, placed on a glass plate and flattened with a wire rod to remove bubbles and ensure that the surface is covered with a layer of SPI solution. The membrane is fixed with clips on all sides and the prepared ePTFE-SPI composite membrane is placed in an oven at 80°C and dried for 24 hours.

5. The method for preparing an enhanced fully sulfonated polyimide proton exchange membrane according to claim 4, characterized in that: The modified ePTFE is fully immersed in the polyimide solution, the immersed ePTFE is taken out and flattened on a glass sheet, and a scraper is used to scrape it to remove bubbles in the membrane. The thickness of the composite membrane is controlled between 14 and 20 microns by scraping with the scraper. The prepared composite membrane is placed in a vacuum oven to dry, so that the solvent can be completely evaporated and the polyimide is solidified on the ePTFE; it is annealed at high temperature to finally obtain a proton exchange membrane.

6. The method for preparing an enhanced fully sulfonated polyimide proton exchange membrane according to claim 4, characterized in that: In the step S1, the pore size of the ePTFE membrane is one of 0.1 micron, 0.22 micron or 0.45 micron.

7. The method for preparing an enhanced fully sulfonated polyimide proton exchange membrane according to claim 4, characterized in that: In step S3, the solvent is one of dimethyl sulfoxide, m-cresol, N,N-dimethylformamide and N-dimethylacetamide.

Citation Information

Patent Citations

  • Proton exchange membrane modified by catechol and polyamine and preparation method thereof

    CN118248911A

  • Composite proton exchange membrane, preparation method and application thereof, and fuel cell

    CN118281269A

  • Negative electrode for secondary battery and electrode assembly containing the same

    KR1020230051978A